PENGARUH TERAPI MUSI K TERHADAP PENURUNAN INTENSITAS NYERI PADA IBU INPARTU KALA I FASE AKTIF - Sofia Mawaddah (POLITEKNIK KESEHATAN KEMENKES PALEMBANG, 2020)
the time leading up to labor, especially in the first stage (when opening), the pain occurs because of the great activity in the mother's body to expel the baby. This pain is getting stronger and stronger, the handling and supervision of labor pain, especially in the first phase of the active phase is very important, because this is a determining point whether a maternity mother can undergo a normal delivery or be assisted with an action due to complications. Method: This study uses a Quasy Experiment with the design of the Two Experiment Pre-Post Test. There were 2 groups in this study, 17 in the first phase active mothers who were given Baluwung distilled music therapy and 17 in the first phase active mothers who were given aromatherapy therapy in rose essential oil. Bivariate analysis using the Mann Whitney test. Results: The study showed the intensity of pain after rose essential oil therapy in First Stage Inpartu mothers The active phase with the resulting probability was 0.623, so it was higher than the intensity of pain after music therapy for First Stage Inpartu mothers active phase. Conclusion: The provision of music therapy is more effective in reducing the intensity of pain in mothers Inpartu Kala I Active phase than the administration of rose essential oil therapy. Keywords: Music Therapy, Labor Pain, Active Phase I Stage